Mapping matters: geoprofiling application in South African serial rape investigation - Glass, Dion (Crime, law and social change, 2021)
Generally, the application of geographic profiling (also known as geoprofiling) is under-researched and its scientific and theoretical foundations, as well as the existing research evidence of its effectiveness, claimed to be inadequate and questionable. Notwithstanding, the present study explored the role of geographic profiling, in the context of the South African serial rapist, by scrutinising, amongst others, the locations of their crime sites. The basic theoretical assumptions underlying geographic profiling, their empirical validity, methods of constructing geographic profiles, and geographic profiling’s accuracy were also probed. Findings presented pioneering criminological insights on how serial rapists navigated to and from their crime sites, which could potentially assist national and international crime investigators with the prediction of subsequent offence locales.